Impact of Cybercrime Legislation on Cybersecurity Measures in Financial Institutions in Pakistan - Aziz, Shaukat (American Journal of Law, 2024)
Purpose: The aim of the study was to assess the impact of cybercrime legislation on cybersecurity measures in financial institutions in Pakistan. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cybercrime laws have provided a robust legal framework that compels financial institutions to adopt comprehensive cybersecurity measures to protect sensitive data and financial assets. The enactment of these laws has led to a marked increase in the implementation of advanced security protocols, including encryption, multi-factor authentication, and continuous monitoring systems. These measures are designed to safeguard against unauthorized access, data breaches, and other cyber threats. Furthermore, cybercrime legislation has promoted greater accountability and transparency within financial institutions. Regulatory requirements often mandate regular security audits, compliance checks, and incident reporting, ensuring that institutions maintain high standards of cybersecurity. This has led to the establishment of dedicated cybersecurity teams and the allocation of significant resources towards developing and maintaining secure IT infrastructures. Additionally, cybercrime laws have fostered enhanced collaboration and information sharing between financial institutions, government agencies, and cybersecurity firms. Implications to Theory, Practice and Policy: Deterrence theory, institutional theory and rational choice theory may be used to anchor future studies on assessing the impact of cybercrime legislation on cybersecurity measures in financial institutions in Pakistan. In practice, financial institutions should prioritize continuous training and awareness programs for their employees to ensure compliance with cybercrime laws. From a policy perspective, it is imperative that cybercrime legislation is regularly updated to address emerging threats and vulnerabilities.